An Analysis of Trend and Sources of Deficit Financing in Nepal - Sutihar, Deo Narayan (Economic Literature, 2016)
Deficit financing has emerged as an important tool of financing government expenditure. In Nepal, the share of fiscal deficit to GDP ratio was 5.5% in FY 2010/11 in compare to 3.6% of FY 2000/01. There are three sources of deficit financing i.e. foreign loan, domestic borrowing and cash balance and their shares to fiscal deficit have found 24.3%, 85.7% and -10.0% respectively in FY 2010/11. The domestic borrowing to budget deficit was found to be very high. The fiscal deficit to expenditure ratio was maximum 30.3% in FY 2000/01 and minimum 16.8% in FY 2010/11 respectively. This exhibits that there was decreasing trend in ratio in the study period. The regression equation has been used to estimate the annual declining rate of fiscal deficit to expenditure ratio. The estimates of the annual average and annual declining rate of deficit/expenditure ratio have been found to be 26.64% and - 0.846% respectively. From the result, it is obvious that fiscal deficit/expenditure ratio has been decreased by 0.846 % annually during the period of 11 years. This trend exhibits that Nepal will try to announce balanced budget in the near future. From the statistical analysis, the value of autocorrelation is found to be 0.427 and its d-statistic has been estimated 1.003, which not significant at 5% level of significance. Thus, the analysis justifies that there is no positive autocorrelation among error terms in the study period. Economic Literature Vol.12 2014: 8-15